Kliniceskaja i profilakticeskaja sportivnaja medicina (opyt VNIIFKa) - Kalinkin, L. A.; Matov, V. V.; Celnokov, V. A. (Teorija i Praktika fiziceskoj Kul'tury, 2003)
The sports medicine is the branch of the clinical medicine whose subject of studying is the organism of a person having set the morphological and functional features, connected to specific influence of the physical exercises and sports. The sport renders the significant influence on the variability of the natural inclinations. The sports medicine brings the serious contribution to the knowledge of especially organized biological norm distinguished a lot from the standard circuit of an usual healthy person. The major social function of physical training and sports is the strengthening of health, the improvement of the physical development and the increase of serviceability is proved to be true by the scientific researches and the clinical supervision. At the same time, sports can cause the changes which are overstepping the limits of the expedient adaptations in an organism. Therefore the subject of the sports medicine is also studying of conditions on the ridge of normal physiology and the pathology, which can arise if physical exercises are applied incorrectly from the point of view of selection of means, techniques, modes. The mainstream of the sports medicine is a versatile studying the general laws and individual displays of physical perfection of a person under the influence of the physical culture and sports.